2018
DOI: 10.1590/1518-8345.2784.3107
|View full text |Cite
|
Sign up to set email alerts
|

Association of preoperative anxiety and depression symptoms with postoperative complications of cardiac surgeries

Abstract: Objective to investigate the associations of preoperative anxiety and depression symptoms with postoperative complications and with sociodemographic and clinical characteristics of patients submitted to the first coronary artery bypass graft.Method observational, analytical and longitudinal study. A consecutive non-probabilistic sample consisted of patients submitted to coronary artery bypass graft. To evaluate the symptoms, the Hospital Anxiety and Depression Scale was used. tracheal intubation for more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
3
16
1
6
Order By: Relevance
“…Previously, there was evidence of increased risk of postoperative nausea in surgical patients with depression symptoms [29]. In contrast with the previous study, we didn't nd differences in the incidence of PONV between the two groups.…”
Section: Discussioncontrasting
confidence: 97%
“…Previously, there was evidence of increased risk of postoperative nausea in surgical patients with depression symptoms [29]. In contrast with the previous study, we didn't nd differences in the incidence of PONV between the two groups.…”
Section: Discussioncontrasting
confidence: 97%
“…Although cardiac surgery usually improves patients’ prognoses, many of these patients experience preoperative anxiety. 1 Indeed, cardiac surgery via a sternotomy is a particularly invasive procedure associated with a high risk of perioperative complications that are sometimes life-threatening. Patients scheduled to undergo such a procedure must make difficult decisions when choosing surgical options that carry risks of severe postoperative complications and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…18,[26][27][28][29][30][31][32][33][34] Poole et al 34 found depression and anxiety symptoms in patients who had undergone OHS; in addition, patients who had higher anxiety also had more negative physical symptoms (e.g., numbness, swelling) after the operation. Similarly, Rodrigues et al 30 found that patients with greater anxiety and depression symptoms before OHS had a higher frequency of complications (e.g., hemodynamic instability, prolonged intubation) after OHS during their stay in the intensive care unit. Anxiety and depression might affect the severity of a patient's symptoms, leading to a poorer quality of life for the patients.…”
Section: Discussionmentioning
confidence: 99%